2016
DOI: 10.18240/ijo.2016.02.09
|View full text |Cite
|
Sign up to set email alerts
|

Ocular biomechanical measurements on post-keratoplasty corneas using a Scheimpflug-based noncontact device

Abstract: The ocular biomechanics remain stable after penetrating keratoplasty according to the CorVis ST measurements. Only two from the ten device-specific parameters have importance in the follow-up period after penetrating keratoplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Corvis ST monitors corneal deformation using an ultra-high-speed Scheimpflug camera with UV-free 455 nm light and provides a set of corneal deformation parameters. Previous studies evaluating corneal biomechanics in post-keratoplasty eyes showed that the deformation amplitude (DA) of transplanted cornea was significantly higher than normal eyes, while the radius at the highest concavity (RHC) was significantly smaller than normal eyes 15,16. This might suggest that corneal transplantation tended to weaken the corneal integrity.…”
Section: Discussionmentioning
confidence: 97%
“…Corvis ST monitors corneal deformation using an ultra-high-speed Scheimpflug camera with UV-free 455 nm light and provides a set of corneal deformation parameters. Previous studies evaluating corneal biomechanics in post-keratoplasty eyes showed that the deformation amplitude (DA) of transplanted cornea was significantly higher than normal eyes, while the radius at the highest concavity (RHC) was significantly smaller than normal eyes 15,16. This might suggest that corneal transplantation tended to weaken the corneal integrity.…”
Section: Discussionmentioning
confidence: 97%
“…There is a relationship between alterations in corneal biomechanics and different factors and ocular parameters such as age [ 12 , 13 ], diabetes [ 14 ], caffeine intake [ 15 ], hormonal changes [ 16 ], level of hydration and fasting [ 17 ], exposure to ultraviolet radiation [ 18 ], intraocular pressure (IOP) [ 13 , 19 ], refractive error [ 20 ], axial length [ 13 ], corneal central thickness and corneal curvature [ 13 ], ocular surgery [ 9 , 10 , 21 ] or orthokeratology [ 22 , 23 ] among others.…”
Section: Introductionmentioning
confidence: 99%